2021
DOI: 10.11646/zootaxa.5081.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Urocleidoides spp. (Monogenea: Dactylogyridae) from the gills of Parodon nasus (Characiformes: Parodontidae) from a Brazilian stream with descriptions of two new species

Abstract: Urocleidoides spp. are reported from the gills of 20 specimens of Parodon nasus (standard length 8.5–12 cm), from the Indiana stream, Tietê River, Upper Paraná River basin, municipality of Botucatu, São Paulo State, Brazil. Urocleoidoides tenuis and two new species were found. Urocleidoides indianensis n. sp. differs from its congeners mainly by the morphology of the vaginal sclerite that is robust, sickle-shaped, and forked at the distal end; and by the bulbous-shaped accessory piece of the male copulatory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 541 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…These authors suggested that future investigation should focus on molecular characterization of stricto sensu and incertae sedis species to test the monophyly of Urocleidoides. The study of Oliveira et al (2021), also based on 28S rDNA analysis, supported the close relationship among some species of Urocleidoides and Cacatuocotyle papilionis Zago et al , 2018, suggesting that Urocleidoides may represent a non-monophyletic group.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…These authors suggested that future investigation should focus on molecular characterization of stricto sensu and incertae sedis species to test the monophyly of Urocleidoides. The study of Oliveira et al (2021), also based on 28S rDNA analysis, supported the close relationship among some species of Urocleidoides and Cacatuocotyle papilionis Zago et al , 2018, suggesting that Urocleidoides may represent a non-monophyletic group.…”
Section: Introductionmentioning
confidence: 75%
“…The clade formed by the species of Urocleidoides showed significant support for both analyses (BI, P = 1 and ML, B = 82). One group consists of the species that parasitize anostomids ( U. paradoxus Kritsky, Thatcher & Boeger, 1986, U. sinus Zago et al , 2020 and U. digitabulum Zago et al , 2020) (BI, P = 1 and ML, B =100), parondontids ( Urocleidoides tenuis Zago et al , 2020; U. indianensis Oliveira et al , 2021 and U. parodoni Oliveira et al , 2021) (BI, P = 1 and ML, B = 100), and erythrinids ( U. vanini n. sp. and U. atilaiamarinoi n.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations